2014
DOI: 10.4081/cp.2014.686
|View full text |Cite
|
Sign up to set email alerts
|

Accidental Intraoral Formalin Injection: A Rare Case Report

Abstract: Formalin is a hazardous chemical that needs cautious handling and special storage.Owing to its disinfectant and fixative (i.e. for preserving pathologic tissue specimens in histopathology) properties, it is widely used in dentistry. Although, the terms formaldehyde and formalin are often confused as being identical, these are different as to the concentrations of the primary component i.e. formaldehyde. In fact, the common fixative available as 10% neutral buffered formalin is actually a 4% solution of formald… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…All of them need special storage and handling. 6 In this case report mistake happened because of negligence and use of untagged multiuse vial containing clear liquid formalin. In dentistry formalin are basically used for preserving extracted teeth (use for educational purpose) and to collect biopsy specimen.…”
Section: Discussionmentioning
confidence: 93%
“…All of them need special storage and handling. 6 In this case report mistake happened because of negligence and use of untagged multiuse vial containing clear liquid formalin. In dentistry formalin are basically used for preserving extracted teeth (use for educational purpose) and to collect biopsy specimen.…”
Section: Discussionmentioning
confidence: 93%
“…Lian and Ngeow 8 (1998), Gupta et al 9 (2011), Arakeri and Brennan 5 (2012), Vaka et al 4 (2014), and Dandriyal et al (2014) 6 have reported similar cases of accidental administrations of formalin during dental procedures. 5 , 7 , 8 Though the extra-oral swelling in our case exceeded that described in any of these cases.…”
Section: Discussionmentioning
confidence: 95%
“…Accidental injury from dental chemicals may occur with a number of substances. 6 Formalin is a chemical commonly used for tissue preservation in dental office. It is also used for preserving extracted teeth, which are for preclinical program, by dental trainees.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations